Aerobic exercise-induced circulating extracellular vesicle combined decellularized dermal matrix hydrogel facilitates diabetic wound healing by promoting angiogenesis - Liu, Haifeng; Wu, Bing; Shi, Xin; Cao, Yanpeng; Zhao, Xin; Liang, Daqiang; Qin, Qihuang; Liang, Xinzhi; Lu, Wei; Wang, Daping; Liu, Jun (Frontiers in Bioengineering and Biotechnology, 2022)
Background: Insufficient blood supply results in unsatisfactory wound healing, especially for challenging wound repair such as diabetic wound defects. Regular exercise training brings a lot of benefits to cardiovascular fitness and metabolic health including attenuation of T2DM progression. Circulating extracellular vesicles (EVs) are postulated to carry a variety of signals involved in tissue crosstalk by their modified cargoes, representing novel mechanisms for the effects of exercise. Prominently, both acute and chronic aerobic exercise training can promote the release of exercise-induced cytokines and enhance the angiogenic function of circulating angiogenic cell–derived EVs. Methods: We investigated the possible angiogenesis potential of aerobic exercise-induced circulating EVs (EXE-EVs) on diabetic wound healing. Circulating EVs were isolated from the plasma of rats subjected to 4 weeks of moderate aerobic exercise or sedentariness 24 h after the last training session. The therapeutic effect of circulating EVs was evaluated in vitro by proliferation, migration, and tube formation assays of human umbilical vein endothelial cells (HUVECs), as well as in vivo by quantification of angiogenesis and cutaneous wound healing in diabetic rats. Results: The number of circulating EVs did not change significantly in exercised rats 24 h post-exercise in comparison with the sedentary rats. Nevertheless, EXE-EVs showed remarkable pro-angiogenic effect by augmenting proliferation, migration, and tube formation of HUVECs. Furthermore, the findings of animal experiments revealed that the EXE-EVs delivered by decellularized dermal matrix hydrogel (DDMH) could significantly promote the repair of skin defects through stimulating the regeneration of vascularized skin. Discussion: The present study is the first attempt to demonstrate that aerobic exercise-induced circulating EVs could be utilized as a cell-free therapy to activate angiogenesis and promote diabetic wound healing. Our findings suggest that EXE-EVs may stand for a potential strategy for diabetic soft tissue wound repair.